Sosialisasi dalam Mengoptimalkan Roda Bisnis pada Masa Pandemi - Asti Gumartifa; Maftuhah Nurrahmi; Bengawan Alfaresi (Universitas Mataram, 2021)
Indonesia has had a lot of changes that have occurred in society. Especially during the current Covid -19 Pandemic. All activities from the process of school, buying, and selling among the community are often carried out online or work from home. The economic income of the family, community, and government has also decreased. The existence of Internet facilities can greatly assist all people in carrying out economic activities to be able to survive during the pandemic. Even these activities are carried out online or still carried out at home. By utilizing social media that is facilitated by the internet, people can continue to carry out buying and selling activities to maintain economic income through online. Here are social media that can be used, namely; Instagram, Facebook, Whats up, and e-mail. Thus, from the use of social media, it can still help the business income even in the pandemic of Covid -19.